2020
DOI: 10.1080/2331186x.2020.1787018
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the relationship between metacognitive strategy awareness, self-regulation and reading proficiency of Iranian EFL learners

Abstract: The research on the effects of metacognitive strategy awareness and self-regulation on second language reading achievements has come to confirmatory conclusions. However, the associations and possible interactions between metacognitive and self-regulatory capacities have been subject of debate. Theoretically, the relationship between the two global skills in affecting learning has ranged from rivaling alternatives to complementary associates. Accordingly, some recent perspectives have delineated the relative p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 37 publications
2
4
1
Order By: Relevance
“…The factor denoted students' effort allocation concerning lexical and syntactic use, grammar correctness, organization, and task knowledge. This result lends support to some existing studies that L2 learners have clear metacognitive awareness about their learning process, including with their L2 writing (Ruan, 2014;Amini et al, 2020). The results of our study enrich the framework of metacognitive experiences in EFL writing as described by Efklides' (2002a,b) taxonomy of metacognitive experiences.…”
Section: Estimate Of Effort Expendituresupporting
confidence: 88%
See 1 more Smart Citation
“…The factor denoted students' effort allocation concerning lexical and syntactic use, grammar correctness, organization, and task knowledge. This result lends support to some existing studies that L2 learners have clear metacognitive awareness about their learning process, including with their L2 writing (Ruan, 2014;Amini et al, 2020). The results of our study enrich the framework of metacognitive experiences in EFL writing as described by Efklides' (2002a,b) taxonomy of metacognitive experiences.…”
Section: Estimate Of Effort Expendituresupporting
confidence: 88%
“…In our study, participants reported three subcategories of online task-specific metacognitive strategies: planning, monitoring, and evaluating, which have also been reported in previous research on metacognitive strategies in L2 learning (Bai et al, 2014;De Silva and Graham, 2015;Amini et al, 2020;Zhao and Liao, 2021). EFL writers in this study tended to plan before writing and monitor their writing process and evaluate their language use after finishing writing tasks; it is noted that online task-specific metacognitive strategies can also be conscious processes.…”
Section: Online Task-specific Metacognitive Strategiessupporting
confidence: 80%
“…For instance, the levels of affect regulation and classroom environment regulation to enhance English speaking performances were both high (Alotumi, 2021;Uztosun, 2020). When self-regulated learning strategies increased, there was a positively corresponding increase in reading comrehension skills (Amini et al, 2020;Yaghi (2021), in listening comprehensions skills (Nosratinia et al, 2015;Yang, 2020), and in writing skills as well (Sun & Wang, 2020;Teng & Zhang, 2020). However, the fact that the subcomponent of Debugging strategies gains the highest mean score (M=3.51) is first noted in the present study.…”
Section: Discussion and Implicationcontrasting
confidence: 37%
“…In the same line, on finding a close relationship between students' self-regulation levels in learning and their academic success by the results of surveying undergraduate students from two universities in Turkey, Tekkol and Demirle (2018) contended that "Learning how to learn is among the fundamental skills of lifelong learning" (p.2). Meanwhile, investigating the relationship between metacognitive strategy awareness, self-regulation, and reading proficiency among Iranian EFL learners, the study by Amini et al (2020) revealed that "participants who had higher scores in self-regulation strategies tended to have higher scores on the reading comprehension" (p.14). Also, Uztosun (2020), surveying 1065 EFL learners via a 20-item scale (of four factors: task value activation, regulation of learning environment, regulation of affect, and regulation of classroom environment), showed that changing both in-class and out-of-class settings is essential for self-regulated learners because it creates more opportunities to practice spoken language.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, SRL is also a vital skill for the workforce (Lord et al, 2010) and a factor of success in foreign language learning (Andrade & Bunker, 2009;Seker, 2016). For example, previous research has shown that SRL strategies contribute to writing proficiency (Sun & Wang, 2020) and reading comprehension (Amini et al, 2020) in foreign language learning. Previous research has indicated that to some extent, teachers enhance SRL (e.g., Ewijk et al, 2013;Perry et al, 2008).…”
Section: Self-regulated Learningmentioning
confidence: 99%